Broadcasting licensing planning in Brazil: historical evolution and perspectives for the services - Pieranti, Octavio Penna [UNESP] (Univ Federal Sergipe, 2015)
This paper has two objectives: (1) analyze the historical evolution of the licenses for the execution of the various broadcasting services in Brazil and (2) discuss a new logic for these licenses, focusing on National Plans of Licenses - PNOs (in Portuguese). Finally, it points to the need to adopt a more rigorous planning for new licenses in accordance with the possibility of more pluralism afforded by digitalization of mass communication.
Keywords: Broadcasting; National Plans of Licenses; Digitalization